Theoretical analysis of the series parasitic resistance in photovoltaic cell - Shannan, N.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
An accurate estimation of the series resistance in the PV model is crucial to the prediction of the maximal output power of the PV module, especially under temperature variation. This Paper proposes a theoretical expression to calculate accurately the value of this resistance. The proposed expression comes from the physical nature of the various elements constructing this resistance, plus the reverse relation of the output power with cell temperature, utilizing manufacturer datasheet only. The proposed expression was tested against experimental measurements and previous work, showing a clear improvement in tracing the series resistance values under varying temperature. © 2017 IEEE.